9. Israeli Apartheid: A Matter of Law - Daniel Machover (For Palestine: Essays from the Tom Hurndall Memorial Lecture Group, 2023)
Israel’s rule over the Palestinian people may be characterized as a regime of apartheid, with its individual actions constituting crimes of apartheid. I was one of the legal advisers to the Russell Tribunal On Palestine (RTOP or ‘Russell Tribunal’) which convened on six occasions, not all of which I was able to assist with (from March 2010 to September 2014) (http://www.russelltribunalonpalestine.com/en/index.html). The third session was held in Cape Town in November 2011 and what I will set out in this chapter is an updated summary of the RTOP’s findings – available in full but not updated via this link http://www.russelltribunalonpalestine.com/en/sessions/south-africa/south-africa-session-%E2%80%94-full-findings The Tribunal made findings with regard to Israel’s policies and practices vis-à-vis the Palestinian people with reference to the international legal prohibition of apartheid under the following headings: The definition and status of apartheid under international law; Application of the definition of apartheid to Israeli policies; and practices vis-à-vis the Palestinian people.